Patient-perceived indicators as a basis for satisfaction assessment of healthcare - Yohanes Kambaru Windi; Baiq Dewi Harnani; Asnani Asnani (International Journal of Public Health Science (IJPHS), 2022)
Since satisfaction is a subjective matter, assessing satisfaction should begin from the individual perception of satisfaction. This study aimed to map the satisfaction indicators perceived by the patients as a foundation to develop instruments to assess health care satisfaction. The study adopted sequential exploratory design of mixed method approach. Thirty patients participated in the interviews and 300 patients for the survey. The thematic analysis identifies 159 items of satisfaction. The items were condensed into 34 indicators and distributed into the five components of the service quality (SERVQUAL) model. A survey containing the 34 indicators were developed to measure their validity and reliability. The Product moment test of validity shows the value of correlation table (rn-2; α=r298; 0.05)=0.095. The values correlation tables are >0.095, meaning the validity is achieved. The Cronbach alpha test shows that the values of all indicators are >0.6, reflecting the reliability of the satisfaction indicators. The study concluded there is variation of satisfaction indicators of health care compared to the established instruments and the identified indicators are valid and reliable.